Strategi Pemberdayaan Masyarakat Berbasis Digital Government Terhadap Pembangunan Desa Sindangheula: Pengabdian - Muhammad Amirul Mukminin; Syifa Salsabila; Sandra Aura Ramadhani; Silvia Ramadhani; Muhammad Dehan Sya’bani; Mohammad Imam Kamaluddin (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This article discusses digital government in empowering communities to support digital-based village development programs, improve public services, and assist communities in addressing information gaps in village areas. Village e-government has been highlighted due to the acceleration of digitalization in villages, particularly in public services. Village governments no longer function as conventional administrative organizers. However, village governments are able to utilize digital technology to improve efficiency, transparency, and accountability in services to the community. This research uses descriptive qualitative methods, interpretation, and in-depth analysis of subjective meanings. Qualitative research uses data collection methods through observation and interviews that researchers have prepared in the form of instruments. Informants are selected using purposive techniques, data collection is carried out through semi-structured interviews, observation, and documentation. Therefore, this article discusses digital government-based empowerment strategies as a wise step in developing village-level digitalization and also implementing the Sustainable Development Goals (SDGs) in the field of village innovation and partnerships in village